1978
DOI: 10.1002/jez.1402040107
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of ciliary pattern in longitudinal fragments of the hypotrichous ciliate, Stylonychia

Abstract: Longitudinal fragments of the hypotrichous ciliate Stylonychia were studied a t various stages of cortical regeneration by Scanning Electron Microscopy. Analysis showed that (except for the oral primordium) all primordial fields responsible for replacing excised ciliature develop in continuity with existing primordia; i.e., all ciliary primordia are derived from segments originally continuous with the oral primordium. This observation leads to the concept of a single primordial field, a "primordium of the cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We have not found continuity between dorsal bristle rows 1, 2, and 3 primordia and the oral or marginal primordia, but we have found that the dorsal bristle rows 1 and 2 primordia initially appear joined at their posterior ends. During regeneration in right longitudinal fragments o f Stylonichia (6), this connection between the dorsal bristle rows 1 and 2 primordia has been described. In this case there is a continuity with the left marginal cirral primordium.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have not found continuity between dorsal bristle rows 1, 2, and 3 primordia and the oral or marginal primordia, but we have found that the dorsal bristle rows 1 and 2 primordia initially appear joined at their posterior ends. During regeneration in right longitudinal fragments o f Stylonichia (6), this connection between the dorsal bristle rows 1 and 2 primordia has been described. In this case there is a continuity with the left marginal cirral primordium.…”
Section: Discussionmentioning
confidence: 93%
“…Our study points out that cortical morphogenesis during excystment of Histriculus similis shows clear differences from cortical morphogenesis during division, regeneration, and reorganization (18,22) with respect to the origin of the cirral primordia. During excystment, the left marginal cirral primordium originates from the oral primordium, as has been described during regeneration of longitudinal fragments in Stylonichia mytilus (6) which lack the old marginal ciliature. 24, 25, 28-34).…”
mentioning
confidence: 76%
“…Reorganization of the marginal cirral rows and dorsal kineties had no peculiarities, occurring as in most dorsomarginalians (e.g. Grimes & Adler, 1978;Jerka-Dziadosz & Frankel, 1969;Kamra & Sapra, 1991;Arora et al, 1999;Blatterer & Foissner, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Zou & Ng (1991) consider physiological reorganization as an ontogenetic process secondarily derived from divisional morphogenesis. It is responsible for renewing a complete conjunct of ciliary elements in intact, non-dividing individuals (Grimes & Adler, 1978). According to Berger (1999), physiological reorganization usually occurs in response to unfavorable environmental (or culture) conditions, such as starvation or other more subtle changes in the medium.…”
mentioning
confidence: 99%
“…They differ-entiated to replace the old ciliature as described by Grimes [ 161 ( Fig. 9, 10, 13,16).…”
Section: Physiological Reorganizationmentioning
confidence: 99%